Personal space of male war veterans with posttraumatic stress disorder - Bogović, Anamarija; Mihanović, Mate; Jokić-Begić, Nataša; Švagelj, Ana (2014)
In this study, the authors examined the preferred interpersonal distances of individuals with combat-related posttraumatic stress disorder (PTSD). Study participants were 151 male war veterans, of whom 83 were suffering from PTSD and 68 were not suffering from PTSD symptoms (control group). Personal space was assessed using a stop- distance technique, where male and female research assistants approached the participants from four directions. Participants with PTSD preferred significantly larger interpersonal distances than did the control group. Participants in both groups maintained larger interpersonal distances when approached by a man than by a woman. The PTSD participants preferred the greatest interpersonal distance when approached from behind, whereas the control group preferred the greatest distance when approached frontally. The authors found these results to be consistent with the self- protective function of personal space.
Projekt MZOS
Projekt MZOS